2023
DOI: 10.14336/ad.2023.1005
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Parkinson’s Disease: From Basic Research to Clinical Practice

Abstract: Parkinson's disease (PD) is a common neurodegenerative disease characterized pathologically by dopaminergic neuron loss and the formation of Lewy bodies, which are enriched with aggregated α-synuclein (α-syn). PD currently has no cure, but therapeutic strategies are available to alleviate symptoms. Early diagnosis can greatly improve therapeutic interventions, but the clinical diagnosis of PD remains challenging and depends mainly on clinical features and imaging tests. Efficient and specific biomarkers are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 182 publications
0
0
0
Order By: Relevance
“…To overcome Parkinson's disease, it is necessary to predict disease risk before onset and achieve early therapeutic interventions. Numerous excellent studies have been reported on diagnostic techniques for Parkinson's disease using analyses of cerebrospinal fluid (CSF), serum, and plasma biomarkers targeting α-synuclein and other related proteins [146][147][148][149]. Additionally, recent studies have demonstrated that severe olfactory impairment is a useful early biomarker for Parkinson's disease dementia [64,65,[150][151][152].…”
Section: Diagnostic Potential Of Fabps As a Prodromal Biomarker For P...mentioning
confidence: 99%
“…To overcome Parkinson's disease, it is necessary to predict disease risk before onset and achieve early therapeutic interventions. Numerous excellent studies have been reported on diagnostic techniques for Parkinson's disease using analyses of cerebrospinal fluid (CSF), serum, and plasma biomarkers targeting α-synuclein and other related proteins [146][147][148][149]. Additionally, recent studies have demonstrated that severe olfactory impairment is a useful early biomarker for Parkinson's disease dementia [64,65,[150][151][152].…”
Section: Diagnostic Potential Of Fabps As a Prodromal Biomarker For P...mentioning
confidence: 99%